Application Of Rule Of Law Principles: National Health Guarantee In Health Services As An Embodiment Of Good Governance - Clarissa, Gavinela; Erliyana, Anna (Riwayat: Educational Journal of History and Humanities, 2024)
Increasing access and quality of health services to meet community needs is important to build good governance. Applying the rule of law principles in health services is used as a guideline for health service delivery organs to carry out their duties and functions. This article discusses the application of the rule of law principles in the National Health Insurance (JKN) program in health services as an embodiment of good governance and the role of the Mobile JKN application in increasing effectiveness and efficiency in the implementation of the National Health Insurance (JKN) program by using descriptive doctrinal research methods to reveal the weaknesses and strengths of the subject matter to be studied